2005
DOI: 10.1111/j.1460-9568.2005.04080.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JNK–c‐Jun pathway during the early phase of neuronal apoptosis induced by PrP106–126 and prion infection

Abstract: Prion diseases are neurodegenerative pathologies characterized by apoptotic neuronal death. Although the late execution phase of neuronal apoptosis is beginning to be characterized, the sequence of events occurring during the early decision phase is not yet well known. In murine cortical neurons in primary culture, apoptosis was first induced by exposure to a synthetic peptide homologous to residues 106-126 of the human prion protein (PrP), PrP106-126. Exposure to its aggregated form induced a massive neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 64 publications
9
44
0
Order By: Relevance
“…Misfolded monomers or oligomeric intermediates appear to be the more probable toxic species. This is consistent with recent data indicating that smaller subfibrillar particles with a mass equivalent to [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] PrP molecules are the most infectious moiety and may be much more toxic than larger amyloid fibrils or plaques [113].…”
Section: Prp In Aggresomessupporting
confidence: 80%
“…Misfolded monomers or oligomeric intermediates appear to be the more probable toxic species. This is consistent with recent data indicating that smaller subfibrillar particles with a mass equivalent to [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] PrP molecules are the most infectious moiety and may be much more toxic than larger amyloid fibrils or plaques [113].…”
Section: Prp In Aggresomessupporting
confidence: 80%
“…Specifically, the dual requirement for conversion to PrP Sc , as well as the association with lipid rafts suggest a subversion of the normal function of PrP C upon misfolding to PrP Sc that involves distortion of signaling events. 12 Subsequent investigations of PrP C and PrP Sc from the perspective of signaling analysis have implicated a number of intracellular kinases and signaling pathways including: Sarcoma (Src), 13 mitogen activated protein kinase (MAPK), 14,15 phosphoinositide-3 kinase (PI3K)/RAC-α series/threonine protein kinase (Akt), 16 c-Jun N-terminal kinase (JNK), 17 and extracellular signal-regulated kinase (Erk). 18 While these investigations strongly indicate that PrP influences the intracellular kinase environment there is no consensus on the specific mechanism and consequences.…”
Section: Resultsmentioning
confidence: 99%
“…A central challenge to understanding the molecular basis of TSEs is determining whether the The PrP 106-126 peptide fragment has been widely utilized as an experimental ligand to model prion effects and this made it an ideal stimulant of PrP C signaling. 17,[20][21][22][23][24] In addition, 6H4 is a well-characterized, commercially-available monoclonal antibody for PrP C . Prion protein specific antibody has been utilized to "activate" PrP C through direct binding for investigations of PrP C function.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous reports using prion-infected primary cultured neurons, antimitotics were used throughout the culture period to suppress the growth of astrocytes (Carimalo et al, 2005;Cronier et al, 2007;Hannaoui et al, 2013), and some of them confirmed the neuronal predominance with astrocytes at 4 -5 % of the cellular composition at an early stage (Cronier et al, 2004). However, antimitotics will be harmful to neurons depending on concentrations and the period of treatment.…”
Section: Discussionmentioning
confidence: 99%